Coccidia-Microbiota Interactions and Their Effects on the Host - Lu, Chenyang; Yan, Yaqun; Jian, Fuchun; Ning, Changshen (Frontiers in Cellular and Infection Microbiology, 2021)
As a common parasitic disease in animals, coccidiosis substantially affects the health of the host, even in the absence of clinical symptoms and intestinal tract colonization. Gut microbiota is an important part of organisms and is closely related to the parasite and host. Parasitic infections often have adverse effects on the host, and their pathogenic effects are related to the parasite species, parasitic site and host-parasite interactions. Coccidia-microbiota-host interactions represent a complex network in which changes in one link may affect the other two factors. Furthermore, coccidia-microbiota interactions are not well understood and require further research. Here, we discuss the mechanisms by which coccidia interact directly or indirectly with the gut microbiota and the effects on the host. Understanding the mechanisms underlying coccidia-microbiota-host interactions is important to identify new probiotic strategies for the prevention and control of coccidiosis.